Mengoptimalkan Pengembangan Pariwisata: Model Implementasi Kegiatan Layanan Berbasis Integrasi Program Studi Politeknik Pariwisata Lombok di Desa Wisata Jeruk Manis - Sirajuddin; Rumba Rumba; Supardi; Komang Mahawira; Endang Sri Wahyuni; Muhammad Ihdal Karomi; Mandra; Jujuk Ferdianto; Yoyok Antoni; Abdul Hanan (PENTAHELIX: Jurnal Ilmiah Pengabdian Pariwisata, 2023)
Community Service Activities in Jeruk Manis Village aim to integrate various tourism potentials, both natural and human resources, in Jeruk Manis Tourism Village so that they can become one unified tourism product. This Community Service is carried out through workshop methods such as lectures, discussions, demonstrations, and practice. PKM activities get output in the form of integration of tourism products in accordance with the potential of Jeruk Manis Tourism Village. This service contributes to providing new understanding and skills to village communities about tourism, especially how to make tour packages, communicate in English, fruit carving, HSK/K3, homestay management, and service ethics.